Lepra Reactions: Mimickers and Mirror to Unmask Complex Cases of Leprosy - Sandhya Kumari; Ghanshyam K. Verma; Ajeet K. Negi; Aakanksha Sharma (Wolters Kluwer Medknow Publications, 2023)
Leprosy is a silent disease with protean manifestations, especially during lepra reactions (LRs). Cases with atypical leprosy or LR simulate a number of conditions misdiagnosed frequently. Here, three classical cases of leprosy are reported for their complex presentation. Leprosy was hidden in Case 1 due to co-existing diabetes. COVID vaccination induced LR unmasked all leprosy lesions, which were extensive, large, bizarre and spreading to various immune zones. Case 2 presented with high-grade fever, tachycardia, generalized erythema and body aches. A detailed workup unveiled his leprosy with a rare presentation of Type 1 lepra reaction (T1LR) with erythroderma and severe systemic symptoms. Case 3 mimicked sarcoidosis and lupus erythematosus (LE) on routine workup. She had facial lesions in the malar area, photosensitivity, joint pains, raised angiotensin-converting enzyme (ACE) levels and positive anti-nuclear antibodies. Peri-appendageal granulomas on histopathology and therapeutic response to multidrug therapy helped in the early diagnosis of leprosy.